Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Untuk Meningkatkan Aktivitas Dan Hasil Belajar Teknik Passing Bola Voli Pada Peserta Didik Kelas XI AKL 1 SMK Darussalam Karangpucung - Dian Imam Saefulah; Kusmiyati; Priska Swarasnantyo (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The purpose of this study was to determine the effect of the NHT type cooperative learning model on learning outcomes of basic volleyball passing techniques. This type of research is a quasi- experimental (quasi-experimental) research design using the non-randomized control group pretest- posttest design. The research subjects were 53 students of class XI AKL 1 SMK Darussalam Karangpucung Kabupaten Cilacap Regency for the 2019/2020 academic year. Learning outcome data were collected through the pretest and posttest. Data analysis used t-test with SPSS 16.0 for Windows. Experiments were carried out 3 times beyond pretest-posttest treatment. Learning outcome data were collected through objective tests, observation and performance. In the experimental group the pretest score was 66.48, while the control group was 64.0. The results of the posttest score in the experimental group obtained an average value of 82.76. While the control group obtained an average value of 78.18. The average normalized gain score obtained in each group is in the experimental group of 0.5 while the control group is 0.4. The significance number obtained is sig 0.001 <0.05. From the research results, it can be concluded that the learning outcomes of students who were given treatment using the NHT type of cooperative learning model were more improved compared to the control group given the conventional learning model. The NHT type cooperative learning model has a significant effect on the improvement of learning outcomes of the basic techniques of volleyball passing in class XI AKL 1 SMK Darussalam Karangpucung Kabupaten Cilacap.